Maidong Dishao Decoction mitigates submandibular gland injury in NOD mice through modulation of gut microbiota and restoration of Th17/Treg immune balance - Yue Zhang; Yunxia Wu; Yin Guan; Yun Lu; Wen Zhu; Fan Ping; Yue Wang (Heliyon)
Background: Primary Sjogren's syndrome (pSS) is a common chronic autoimmune disease that presents limited treatment options and poses significant challenges for patients. Maidong Dishao Decoction (MDDST), a traditional Chinese medicine compound, has demonstrated potential in alleviating dryness symptoms associated with pSS. Therefore, it is important to study the specific mechanism of its therapeutic effect. Objective: This study aims to investigate the effects of MDDST on gut microbiota, short-chain fatty acids (SCFAs), and the Th17/Treg immune balance in non-obese diabetes (NOD) mice. Methods: The study employed ultrahigh-performance liquid chromatography coupled with quadrupole-exactive mass spectrometry (UHPLC-QE-MS) to identify the primary components of MDDST. Subsequently, hematoxylin and eosin (HE) staining, enzyme-linked immunosorbent assays (ELISA), and flow cytometry analyses were conducted to evaluate the therapeutic effects of MDDST in NOD mice. Additionally, 16S rDNA sequencing and gas chromatography-mass spectrometry (GC-MS) were utilized to assess the influence of MDDST on gut microbiota and SCFAs. Finally, fecal microbiota transplantation (FMT) and SCFA-based interventions were performed to elucidate the mechanisms through which MDDST exerts its effects. Results: The research findings demonstrate that MDDST exerts therapeutic effects on NOD mice, primarily manifested as reduced inflammation, decreased water intake, ameliorated pathological changes and lowered levels of Sjogren's syndrome antigen A (SSA) and immunoglobulin G (IgG). Additionally, MDDST significantly decreased serum levels of interleukin-6 (IL-6) and interleukin-17 (IL-17), while enhancing levels of interleukin-10 (IL-10) and transforming growth factor beta (TGF-β), thereby regulating the Th17/Treg immune balance. Further investigations revealed that MDDST treatment induces alterations in gut microbiota composition and elevates SCFA levels in the gut. Subsequent FMT and SCFA intervention experiments demonstrated a downregulation of pSS-related phenotypes. Conclusion: In summary, MDDST demonstrates protective effects against pSS by restoring the balance between Th17 and Treg cells. The therapeutic effects can be partially attributed to its regulation of gut microbiota and SCFAs. Our finding provides a new option for treating pSS.